ANALISIS TAHAPAN INTRUKSIONAL DAN FAKTOR-FAKTOR MOTIVASI PENYULUHAN SISTEM PERTANIAN ORGANIK PADA KELOMPOK TANI KEDISAN MANDIRI KECAMATAN TEGALLALANG, KABUPATEN GIANYAR: ANALISIS TAHAPAN INTRUKSIONAL DAN FAKTOR-FAKTOR MOTIVASI PENYULUHAN SISTEM PERTANIAN ORGANIK PADA KELOMPOK TANI KEDISAN MANDIRI KECAMATAN TEGALLALANG, KABUPATEN GIANYAR - Utari, Ni Kadek Sri; Wibawa, Made Satria (Universitas Duta Bangsa Surakarta, 2025)
Conventional agriculture is increasingly dependent on the intensive use of chemical fertilizers. The increased use of chemical fertilizers has caused serious problems, ranging from soil fertility degradation to environmental pollution, which ultimately has a negative impact on farmers' health. On the other hand, organic farming systems have emerged as an alternative that integrates environmental conservation principles while improving the quality and added value of agricultural products. Extension plays an important role in efforts to transition to organic farming, Sugino (2021) stated that the extension approach must be arranged in such a way that farmers not only gain new knowledge but are also motivated to apply it consistently. This study aims to analyze in depth the instructional stages and motivational factors that influence the success of organic farming system extension at the Kedisan Mandiri Farmers Group in Tegallalang District, Gianyar Regency. Determination of key informants was carried out using the purposive sampling method to ensure that the selected key informants have characteristics that are appropriate and relevant to the focus of the study, namely agricultural extension and the head of the Kedisan Mandiri Farmers Group. Based on the results of data reduction and presentation, it can be concluded that the instructional stages in organic agricultural extension activities at the Kedisan Mandiri Farmer Group have been implemented systematically and contextually. Extension workers have succeeded in designing activities that are in accordance with the needs of farmers and are able to create a participatory learning atmosphere. In addition, high motivation from extension workers and participants is the main factor in the success of extension activities. External factors such as support from the village government, adequate extension facilities, and social recognition from external parties also strengthen the motivation and sustainability of the extension program.